Annual impact of scribes on physician productivity and revenue in a cardiology clinic - Bank AJ; Gage RM (Dove Medical Press, 2015)
Alan J Bank, Ryan M Gage United Heart and Vascular Clinic, St Paul, MN, USA Objective: Scribes are increasingly being used in clinics to assist physicians with documentation during patient care. The annual effect of scribes in a real-world clinic on physician productivity and revenue has not been evaluated. Methods: We performed a retrospective study comparing the productivity during routine clinic visits of ten cardiologists using scribes vs 15 cardiologists without scribes. We tracked patients per hour and patients per year seen per physician. Average direct revenue (clinic visit) and downstream revenue (cardiovascular revenue in the 2 months following a clinic visit) were measured in 486 patients and used to calculate annual revenue generated as a result of increased productivity. Results: Physicians with scribes saw 955 new and 4,830 follow-up patients vs 1,318 new and 7,150 follow-up patients seen by physicians without scribes. Physicians with scribes saw 9.6% more patients per hour (2.50±0.27 vs 2.28±0.15, P<0.001). This improved productivity resulted in 84 additional new and 423 additional follow-up patients seen, 3,029 additional work relative value units (wRVUs) generated, and an increased cardiovascular revenue of $1,348,437. Physicians with scribes also generated an additional revenue of $24,257 by producing clinic notes that were coded at a higher level. Total additional revenue generated was $1,372,694 at a cost of $98,588 for the scribes. Conclusion: Physician productivity in a cardiology clinic was ~10% higher for physicians using scribes. This improved productivity resulted in 84 additional new and 423 additional follow-up patients seen in 1 year. The use of scribes resulted in the generation of 3,029 additional wRVUs and an additional annual revenue of $1,372,694 at a cost of $98,588. Keywords: physician productivity, medical economics, scribe